Biomechanical analysis of tension-compression asymmetry, anisotropy and heterogeneity of bone reconstruction in response to periprosthetic fracture repair - Zolochevsky, Olexander; Martynenko, Alexander (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
Introduction. Bone repair after periprosthetic fracture is a critical issue in orthopedics. Objectives. So there is a need for research to provide new medical solutions, especially in the context of population ageing in the Ukraine. The importance of biomechanics which is concerned with the application of principles, concepts and methods of mechanics of solid and fluid to the human body in motion and at rest is well recognized as a foundation for further experimental and theoretical research in the skeletal tissues. Materials and methods. Different aspects of biomechanics require different concepts and methods of mechanics of solid and fluid to be used. Remodeling occurs significantly throughout lifetime of bone that is why it can be regarded as a primary determinant of the mechanical properties of bone and implant. Biomechanical analysis given in this review has been concerned with understanding on how mechanical signals and molecular mechanisms affect the healing of Vancouver periprosthetic femoral fracture of B1 and C-type with the use of internal fixation through a less invasive stabilization system (LISS)-plate, which is screwed into the artificial hip joint. Results. Identification of such parameters as mechanical properties of bone, titanium alloys (hip prosthesis, coating, LISS-plate, screws) and implant/biomaterial interface with bone under mechanical and biochemical loading that are very essential for predicting arthroplasty outcomes were investigated experimentally considering elastoplastic deformation, creep, fatigue and ratcheting, as well as, damage development in materials under discussion. Among the basic deformation features were tension-compression asymmetry, anisotropy and heterogeneity of mechanical properties. We used the three-dimensional finite element model derived from the reconstruction of treatment and magnetic resonance (tomographic) images. Conclusions. As a result of this model analysis, it was found that treatment rate of periprosthetic femoral fractures after total hip arthroplasty with the use of LISS-plates and screws for internal fixation may be controlled by means of ABAQUS (or ANSYS) software package to reproduce the characteristic features of bone and implant in bone reconstruction in order to improve the fracture healing rate and shorten treatment duration.